Bisphosphonate Treatment in a Patient Affected by MPS IVA with Osteoporotic Phenotype - Albina Tummolo; Orazio Gabrielli; Alberto Gaeta; Maristella Masciopinto; Lucia Zampini; Luigi Michele Pavone; Paola Di Natale; Francesco Papadia (Case Reports in Medicine)
Morquio A syndrome (Mucopolysaccharidosis type IVA) (MPS IVA) is a rare inherited metabolic disorder characterized by the defective degradation of keratan sulfate and chondroitin-6-sulfate. Classically, MPS IVA patients present with severe multisystemic involvement and have a short life expectancy. Attenuated forms with clinical features limited to minor skeletal abnormalities and short stature have also been described, sometimes associated to an early-onset osteoporotic phenotype. No treatment with allogenic bone marrow transplantation or gene therapy is currently available for Morquio A syndrome, and enzyme replacement therapy is under evaluation. We report a case of MPS IVA, who manifested tardily attenuated phenotype and significant bone mass reduction, which was treated with a bisphosphonate (BPN), resulting in an improvement of X-ray skeletal aspects and functional bone performance. We suggest that the use of bisphosphonates may be an interesting supportive therapeutic option for Morquio A patients with osteoporotic phenotype, but further studies involving more patients are necessary to confirm our findings.